HUMAN ANATOMY AND PHYSIOLOGY: STRUCTURE-FUNCTION HARMONY - Mahsudov Valijon Gafurjonovich, (TADQIQOTLAR, 2026)
Abstract: This work is devoted to the study of the harmony of structure and function between human anatomy and physiology, showing that the structure of cells, tissues, organs and organ systems determines their physiological functions. The study highlights the principle of structure-function as one of the basic concepts of biomedical sciences  and  analyzes  the  adaptation  of  anatomical  features  in  the  human  body  to specific functional needs. The connection between structure and function is explained using  the  example  of  the  cardiovascular,  respiratory,  nervous  and  musculoskeletal systems.  Understanding  this  connection  is  important  for  the  formation  of  clinical thinking  for  medical  students.  It  is  also  emphasized  that  disorders  in  anatomical structures lead to disruption of physiological functions and form the basis of many diseases. In general, the integration of anatomy and physiology serves to provide a deeper understanding of the human body and increase the effectiveness of medical education.